Implementation of an Antimicrobial Stewardship Program in a Neonatal Intensive Care Unit. (26th July 2017) - Nzegwu, Nneka I.; Rychalsky, Michelle R.; Nallu, Loren A.; Song, Xuemei; Deng, Yanhong; Natusch, Amber M.; Baltimore, Robert S.; Paci, George R.; Bizzarro, Matthew J.
Abstract : OBJECTIVE: To evaluate antimicrobial utilization and prescription practices in a neonatal intensive care unit (NICU) after implementation of an antimicrobial stewardship program (ASP). DESIGN: Quasi-experimental, interrupted time-series study. SETTING: A 54-bed, level IV NICU in a regional academic and tertiary referral center. PATIENTS AND PARTICIPANTS: All neonates prescribed antimicrobials from January 1, 2011, to June 30, 2016, were eligible for inclusion. INTERVENTION: Implementation of a NICU-specific ASP beginning July 2012. METHODS: We convened a multidisciplinary team and developed guidelines for common infections, with a focus on prescriber audit and feedback. We conducted an interrupted time-series analysis to evaluate the effects of our ASP. Our primary outcome measure was days of antibiotic therapy (DOT) per 1, 000 patient days for all and for select antimicrobials. Secondary outcomes included provider-specific antimicrobial prescription events for suspected late-onset sepsis (blood or cerebrospinal fluid infection at >72 hours of life) and guideline compliance. RESULTS: Antibiotic utilization decreased by 14.7 DOT per 1, 000 patient days during the stewardship period, although this decrease was not statistically significant ( P =.669). Use of ampicillin, the most commonly antimicrobial prescribed in our NICU, decreased significantly, declining by 22.5 DOT per 1, 000 patient days ( P =.037). Late-onset sepsis evaluation and prescription events per 100 NICU days of clinical service decreased significantly ( P <.0001), with an average reduction of 2.65 evaluations per year per provider. Clinical guidelines were adhered to 98.75% of the time. CONCLUSIONS: Implementation of a NICU-specific antimicrobial stewardship program is feasible and can improve antibiotic prescribing practices. Infect Control Hosp Epidemiol 2017;38:1137–1143